Does the Teaching of History in Turkey Need Reform?. Issue 1 (1st December 2001) - Demircioğlu, İsmail
There has been some dissatisfaction with the teaching of history that has been voiced by scholars since the 1970s in Turkey. Despite the long interval, these problems are still a feature of this field for the following reasons: government negligence, lack of well- qualified staff for the teaching of history, the preparation of history teachers and lack of an up-to-date curriculum for both school history and secondary school history teacher education institutions. Through this paper, it is intended to examine some of the controversies about the teaching of history in the last three decades.